Microwave Heating Time Dependent Synthesis of Various Dimensional Graphene Oxide Supported Hierarchical Zno Nanostructures and Its Photoluminescence Studies - Singh, D (Elsevier Ltd, 2016)
Microwave heating reaction time dependent various graphene oxide based zinc oxide (G-ZnO) heterostructures such as graphene oxide-ZnO microcubes (GZMC), graphene oxide-ZnO nanoflakes (GZNF) and graphene oxide-ZnO nanoneedles (GZNN) are synthesized by simple and cost effective microwave assisted exfoliation method. These heterostructures supported on graphene oxide nanosheets (GNSs) represent three dimensional (3D) ZnO microcubes and various confined two dimensional (2D) nanoflakes and one dimensional (1D) ZnO nanoneedles like structures. The recorded PL intensity variations show the strong evidence of the interfaces interaction between graphene oxide and ZnO heterostructures. However the differences in the PL intensities are also caused by the 3D and various confined G-ZnO heterostructures. The photoluminescence characterization of GZMC, GZNF and GZNN nanostructures exhibit a decrement in the PL intensity. The PL intensity of the GZNN is lowered by 67.50% and 39.7%to the GZMC and GZNF nanostructures respectively. The results show that ZnO heterostructures grown on GNSs with different morphologies and dimensionalities exhibit the variation in PL intensity due to preventing a direct recombination of the electrons and holes in ZnO. A tentative growth mechanism has been given for the growth of various graphene based zinc oxide heterostructures. © 2016 Elsevier Ltd